ANALYSIS OF INPATIENT NUTRITION SERVICES MANAGEMENT AT LUBUK PAKAM GRANDMED HOSPITAL - Andreais Boffil Cholilullah; Ika Nur Saputri; Raini Panjaitan; Asrida . (JURNAL KESMAS DAN GIZI (JKG), 2022)
Management of nutrition services in hospitals includes planning, organizing, implementing, monitoring, and evaluating. Management of nutrition services is very much needed by a hospital because without management the achievement of goals will be more difficult. This study aims to analyze the management of inpatient nutrition services at Grandmed Lubuk Pakam Hospital. This type of research is a mix method research with a concurrent embedded design. Data was collected through interviews, observation, and document review with reference to hospital nutrition guidelines (PGRS). From the results of the research that the planning, direction and control management process has been going well, the organizing management process is good enough, it's just that the existing nutritional needs are not in accordance with the Management standards and Hospital Nutrition Guidelines. This is supported by quantitative research that aims to describe the quality of inpatient nutrition services. From the results of the study, it can be seen that from 67 respondents, 37 (55.2%) respondents stated that they were sufficient for the quality of inpatient nutrition services.